Adaptation Strategies in Students with Motor Functional Diversity - Franco Buitrago, Maribel; Muñoz Jara, Luisa María; Vargas Pérez, Nicol Dayana; García García, Nancy (Investigación y Educación en Enfermería, 2023)
Objective. The work sough to know the adaptation strategies of students from Universidad del Quindío with motor functional diversity. Method. Descriptive qualitative study with a phenomenological approach. Data were collected through an in-depth interview with nine undergraduate students with moderate motor functional diversity, in face-to-face class attendance modality during the period 2022-2 at Universidad del Quindío (Colombia) with age ≥ 18 years and having scored from 20 - 40 in the Barthel index. The definition of the number of participants was conducted through theoretical saturation. Results. Seven categories emerged from the descriptive analysis of the interviews: 1) support; 2) affection; 3) life project; 4) personal growth; 5) spirituality; 6) autonomy, and 7) education. Together, they reveal important aspects on the way students have adapted to the university campus and how interpersonal relations can contribute to promoting resilience processes Conclusion. Support and affection provided by the social setting play a fundamental role in the adaptation of students with motor functional diversity, improving their mental health, generating resilience, and increasing their self-esteem. Noting that in spite of lifestyle changes after the acquisition of the diversity, the students set novel goals and develop new abilities that contribute to complying with their life project; likewise, they have set into practice and can recognize their coping mechanisms, acquiring qualities, like resilience and autonomy.